Pengembangan Pengembangan Bahan Ajar Digital Materi Termodinamika Berbasis Aplikasi Notion Dengan Instrumen Higher Order Thinking Skill Pada Siswa SMA di Kelas XI - Grace Novely Aswin Siallagan; Laili Komariyah; Atin Nuryadin (UNIB Press, 2024)
Teaching materials need to be developed to support the learning process to encourage students to be more active and creative in the learning process supported by applications and instruments that can improve the quality of student learning to be interactive. This study uses research and development (R & D) methods with a development model, namely ADDIE (Analysis, Design, development, Implementation, Evaluation). This study aims to determine: 1) the validity of digital teaching materials, 2) the results of students' responses to digital teaching materials using the Notion application based on the Higher Order Thinking Skill instrument in class XI students in SMA. The sample in this study was 31 students from class XI MIPA 2 SMA Negeri 9 North Samarinda. The validity and results of student responses were collected using a questionnaire The results of this study indicate: 1) the average percentage of digital teaching materials with the validity of material and media experts is 86.25% with the assessment criteria that is very feasible to be implemented to students, 2) the results of student responses to digital teaching materials are 80% with the criteria for student response results are very positive, with the conclusion that this teaching material can be implemented to students to support the learning process based on the results of validation and student response questionnaires.